Earthquake Resistant Buildings Dynamic Analyses, Numerical Computations, Codified Methods, Case Studies and Examples - Bangash, M.Y.H (Springer Berlin Heidelberg Imprint: Springer, 2011)
This concise work provides a general introduction to the design of buildings which must be resistant to the effect of earthquakes. A major part of this design involves the building structure which has a primary role in preventing serious damage or structural collapse. Much of the material presented in this book examines building structures. Due to the recent discovery of vertical components, it examines not only the resistance to lateral forces but also analyses the disastrous influence of vertical components. Much attention is directed to the Eurocode 8. The work is written for Practicing Civil, Structural, and Mechanical Engineers, Seismologists and Geoscientists. It serves as a knowledge source for graduate students and their instructors.